Zeta and Related Functions - 25.8 Sums

From testwiki
Revision as of 12:04, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
25.8.E1 k = 2 ( ζ ( k ) - 1 ) = 1 superscript subscript 𝑘 2 Riemann-zeta 𝑘 1 1 {\displaystyle{\displaystyle\sum_{k=2}^{\infty}\left(\zeta\left(k\right)-1% \right)=1}}
\sum_{k=2}^{\infty}\left(\Riemannzeta@{k}-1\right) = 1

sum(Zeta(k)- 1, k = 2..infinity) = 1
Sum[Zeta[k]- 1, {k, 2, Infinity}, GenerateConditions->None] == 1
Failure Successful Successful [Tested: 0] Successful [Tested: 1]
25.8.E2 k = 0 Γ ( s + k ) ( k + 1 ) ! ( ζ ( s + k ) - 1 ) = Γ ( s - 1 ) superscript subscript 𝑘 0 Euler-Gamma 𝑠 𝑘 𝑘 1 Riemann-zeta 𝑠 𝑘 1 Euler-Gamma 𝑠 1 {\displaystyle{\displaystyle\sum_{k=0}^{\infty}\frac{\Gamma\left(s+k\right)}{(% k+1)!}\left(\zeta\left(s+k\right)-1\right)=\Gamma\left(s-1\right)}}
\sum_{k=0}^{\infty}\frac{\EulerGamma@{s+k}}{(k+1)!}\left(\Riemannzeta@{s+k}-1\right) = \EulerGamma@{s-1}
( s + k ) > 0 , ( s - 1 ) > 0 formulae-sequence 𝑠 𝑘 0 𝑠 1 0 {\displaystyle{\displaystyle\Re(s+k)>0,\Re(s-1)>0}}
sum((GAMMA(s + k))/(factorial(k + 1))*(Zeta(s + k)- 1), k = 0..infinity) = GAMMA(s - 1)
Sum[Divide[Gamma[s + k],(k + 1)!]*(Zeta[s + k]- 1), {k, 0, Infinity}, GenerateConditions->None] == Gamma[s - 1]
Failure Aborted Successful [Tested: 1] Skipped - Because timed out
25.8.E3 k = 0 ( s ) k ζ ( s + k ) k ! 2 s + k = ( 1 - 2 - s ) ζ ( s ) superscript subscript 𝑘 0 Pochhammer 𝑠 𝑘 Riemann-zeta 𝑠 𝑘 𝑘 superscript 2 𝑠 𝑘 1 superscript 2 𝑠 Riemann-zeta 𝑠 {\displaystyle{\displaystyle\sum_{k=0}^{\infty}\frac{{\left(s\right)_{k}}\zeta% \left(s+k\right)}{k!2^{s+k}}=(1-2^{-s})\zeta\left(s\right)}}
\sum_{k=0}^{\infty}\frac{\Pochhammersym{s}{k}\Riemannzeta@{s+k}}{k!2^{s+k}} = (1-2^{-s})\Riemannzeta@{s}
s 1 𝑠 1 {\displaystyle{\displaystyle s\neq 1}}
sum((pochhammer(s, k)*Zeta(s + k))/(factorial(k)*(2)^(s + k)), k = 0..infinity) = (1 - (2)^(- s))*Zeta(s)
Sum[Divide[Pochhammer[s, k]*Zeta[s + k],(k)!*(2)^(s + k)], {k, 0, Infinity}, GenerateConditions->None] == (1 - (2)^(- s))*Zeta[s]
Failure Successful
Failed [1 / 6]
Result: -.1666666667
Test Values: {s = -2}

Successful [Tested: 6]
25.8.E4 k = 1 ( - 1 ) k k ( ζ ( n k ) - 1 ) = ln ( j = 0 n - 1 Γ ( 2 - e ( 2 j + 1 ) π i / n ) ) superscript subscript 𝑘 1 superscript 1 𝑘 𝑘 Riemann-zeta 𝑛 𝑘 1 superscript subscript product 𝑗 0 𝑛 1 Euler-Gamma 2 superscript 𝑒 2 𝑗 1 𝜋 𝑖 𝑛 {\displaystyle{\displaystyle\sum_{k=1}^{\infty}\frac{(-1)^{k}}{k}(\zeta\left(% nk\right)-1)=\ln\left(\prod_{j=0}^{n-1}\Gamma\left(2-e^{(2j+1)\pi i/n}\right)% \right)}}
\sum_{k=1}^{\infty}\frac{(-1)^{k}}{k}(\Riemannzeta@{nk}-1) = \ln@{\prod_{j=0}^{n-1}\EulerGamma@{2-e^{(2j+1)\pi i/n}}}

sum(((- 1)^(k))/(k)*(Zeta(n*k)- 1), k = 1..infinity) = ln(product(GAMMA(2 - exp((2*j + 1)*Pi*I/n)), j = 0..n - 1))
Sum[Divide[(- 1)^(k),k]*(Zeta[n*k]- 1), {k, 1, Infinity}, GenerateConditions->None] == Log[Product[Gamma[2 - Exp[(2*j + 1)*Pi*I/n]], {j, 0, n - 1}, GenerateConditions->None]]
Failure Failure Successful [Tested: 1]
Failed [1 / 3]
Result: Plus[-0.6931471805599453, NSum[Times[Power[-1, k], Power[k, -1], Plus[-1, Zeta[k]]]
Test Values: {k, 1, DirectedInfinity[1]}, Rule[GenerateConditions, None]]], {Rule[n, 1]}

25.8.E5 k = 2 ζ ( k ) z k = - γ z - z ψ ( 1 - z ) superscript subscript 𝑘 2 Riemann-zeta 𝑘 superscript 𝑧 𝑘 𝑧 𝑧 digamma 1 𝑧 {\displaystyle{\displaystyle\sum_{k=2}^{\infty}\zeta\left(k\right)z^{k}=-% \gamma z-z\psi\left(1-z\right)}}
\sum_{k=2}^{\infty}\Riemannzeta@{k}z^{k} = -\EulerConstant z-z\digamma@{1-z}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
sum(Zeta(k)*(z)^(k), k = 2..infinity) = - gamma*z - z*Psi(1 - z)
Sum[Zeta[k]*(z)^(k), {k, 2, Infinity}, GenerateConditions->None] == - EulerGamma*z - z*PolyGamma[1 - z]
Failure Successful Successful [Tested: 1] Successful [Tested: 1]
25.8.E6 k = 0 ζ ( 2 k ) z 2 k = - 1 2 π z cot ( π z ) superscript subscript 𝑘 0 Riemann-zeta 2 𝑘 superscript 𝑧 2 𝑘 1 2 𝜋 𝑧 𝜋 𝑧 {\displaystyle{\displaystyle\sum_{k=0}^{\infty}\zeta\left(2k\right)z^{2k}=-% \tfrac{1}{2}\pi z\cot\left(\pi z\right)}}
\sum_{k=0}^{\infty}\Riemannzeta@{2k}z^{2k} = -\tfrac{1}{2}\pi z\cot@{\pi z}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
sum(Zeta(2*k)*(z)^(2*k), k = 0..infinity) = -(1)/(2)*Pi*z*cot(Pi*z)
Sum[Zeta[2*k]*(z)^(2*k), {k, 0, Infinity}, GenerateConditions->None] == -Divide[1,2]*Pi*z*Cot[Pi*z]
Failure Failure Error
Failed [1 / 1]
Result: Plus[4.8091767343044744*^-17, NSum[Times[Power[0.5, Times[2, k]], Zeta[Times[2, k]]]
Test Values: {k, 0, DirectedInfinity[1]}, Rule[GenerateConditions, None]]], {Rule[z, 0.5]}

25.8.E7 k = 2 ζ ( k ) k z k = - γ z + ln Γ ( 1 - z ) superscript subscript 𝑘 2 Riemann-zeta 𝑘 𝑘 superscript 𝑧 𝑘 𝑧 Euler-Gamma 1 𝑧 {\displaystyle{\displaystyle\sum_{k=2}^{\infty}\frac{\zeta\left(k\right)}{k}z^% {k}=-\gamma z+\ln\Gamma\left(1-z\right)}}
\sum_{k=2}^{\infty}\frac{\Riemannzeta@{k}}{k}z^{k} = -\EulerConstant z+\ln@@{\EulerGamma@{1-z}}
| z | < 1 , ( 1 - z ) > 0 formulae-sequence 𝑧 1 1 𝑧 0 {\displaystyle{\displaystyle|z|<1,\Re(1-z)>0}}
sum((Zeta(k))/(k)*(z)^(k), k = 2..infinity) = - gamma*z + ln(GAMMA(1 - z))
Sum[Divide[Zeta[k],k]*(z)^(k), {k, 2, Infinity}, GenerateConditions->None] == - EulerGamma*z + Log[Gamma[1 - z]]
Failure Successful Successful [Tested: 1] Successful [Tested: 1]
25.8.E8 k = 1 ζ ( 2 k ) k z 2 k = ln ( π z sin ( π z ) ) superscript subscript 𝑘 1 Riemann-zeta 2 𝑘 𝑘 superscript 𝑧 2 𝑘 𝜋 𝑧 𝜋 𝑧 {\displaystyle{\displaystyle\sum_{k=1}^{\infty}\frac{\zeta\left(2k\right)}{k}z% ^{2k}=\ln\left(\frac{\pi z}{\sin\left(\pi z\right)}\right)}}
\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{k}z^{2k} = \ln@{\frac{\pi z}{\sin@{\pi z}}}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
sum((Zeta(2*k))/(k)*(z)^(2*k), k = 1..infinity) = ln((Pi*z)/(sin(Pi*z)))
Sum[Divide[Zeta[2*k],k]*(z)^(2*k), {k, 1, Infinity}, GenerateConditions->None] == Log[Divide[Pi*z,Sin[Pi*z]]]
Failure Successful Successful [Tested: 1] Successful [Tested: 1]
25.8.E9 k = 1 ζ ( 2 k ) ( 2 k + 1 ) 2 2 k = 1 2 - 1 2 ln 2 superscript subscript 𝑘 1 Riemann-zeta 2 𝑘 2 𝑘 1 superscript 2 2 𝑘 1 2 1 2 2 {\displaystyle{\displaystyle\sum_{k=1}^{\infty}\frac{\zeta\left(2k\right)}{(2k% +1)2^{2k}}=\frac{1}{2}-\frac{1}{2}\ln 2}}
\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)2^{2k}} = \frac{1}{2}-\frac{1}{2}\ln@@{2}

sum((Zeta(2*k))/((2*k + 1)*(2)^(2*k)), k = 1..infinity) = (1)/(2)-(1)/(2)*ln(2)
Sum[Divide[Zeta[2*k],(2*k + 1)*(2)^(2*k)], {k, 1, Infinity}, GenerateConditions->None] == Divide[1,2]-Divide[1,2]*Log[2]
Failure Successful Successful [Tested: 0] Successful [Tested: 1]
25.8.E10 k = 1 ζ ( 2 k ) ( 2 k + 1 ) ( 2 k + 2 ) 2 2 k = 1 4 - 7 4 π 2 ζ ( 3 ) superscript subscript 𝑘 1 Riemann-zeta 2 𝑘 2 𝑘 1 2 𝑘 2 superscript 2 2 𝑘 1 4 7 4 superscript 𝜋 2 Riemann-zeta 3 {\displaystyle{\displaystyle\sum_{k=1}^{\infty}\frac{\zeta\left(2k\right)}{(2k% +1)(2k+2)2^{2k}}=\frac{1}{4}-\frac{7}{4\pi^{2}}\zeta\left(3\right)}}
\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)(2k+2)2^{2k}} = \frac{1}{4}-\frac{7}{4\pi^{2}}\Riemannzeta@{3}

sum((Zeta(2*k))/((2*k + 1)*(2*k + 2)*(2)^(2*k)), k = 1..infinity) = (1)/(4)-(7)/(4*(Pi)^(2))*Zeta(3)
Sum[Divide[Zeta[2*k],(2*k + 1)*(2*k + 2)*(2)^(2*k)], {k, 1, Infinity}, GenerateConditions->None] == Divide[1,4]-Divide[7,4*(Pi)^(2)]*Zeta[3]
Failure Successful Successful [Tested: 0] Successful [Tested: 1]